The changing demand for livestock products - Mohd Dahan, Mohamed Mahyuddin (Universiti Pertanian Malaysia, 1994)
Livestock is and important and integral component of the agricultural sector providing gainful employment and producing useful animal protein foods to the population. Livestock farming includes the production of poultry meat, eggs, pork, beef, mutton and milk as food items.